A Similar Genetic Architecture Underlies the Convergent Evolution of the Selfing Syndrome in Capsella. Issue 4 (21st January 2020) - Woźniak, Natalia Joanna; Kappel, Christian; Marona, Cindy; Altschmied, Lothar; Neuffer, Barbara; Sicard, Adrien
Abstract : Independent evolutionary reductions of petal size in the genus Capsella are associated with convergent evolution of gene expression and underlain by similar genetic architectures. Abstract: Whether, and to what extent, phenotypic evolution follows predictable genetic paths remains an important question in evolutionary biology. Convergent evolution of similar characters provides a unique opportunity to address this question. The transition to selfing and the associated changes in flower morphology are among the most prominent examples of repeated evolution in plants. In this study, we take advantage of the independent transitions to self-fertilization in the genus Capsella to compare the similarities between parallel modifications of floral traits and test for genetic and developmental constraints imposed on flower evolution in the context of the selfing syndrome. Capsella rubella and Capsella orientalis emerged independently but evolved almost identical flower characters. Not only is the evolutionary outcome identical but the same developmental strategies underlie the convergent reduction of flower size. This has been associated with convergent evolution of gene expression changes. The transcriptomic changes common to both selfing lineages are enriched in genes with low network connectivity and with organ-specific expression patterns. Comparative genetic mapping also suggests that, at least in the case of petal size evolution, these similarities have a similar genetic basis. Based on these results, we hypothesize that the limited availability of low-pleiotropy paths predetermines closely related species to similar evolutionary outcomes.